Aluminum color physical sample for CW1-6, SF1-5, SF6-10B, SF13-15 & SF11-12 (RFA - 03_Rev A) - Arman Engineering Ltd. (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.